2017
DOI: 10.22146/ijbiotech.26106
|View full text |Cite
|
Sign up to set email alerts
|

Brazilein in Combination with Cisplatin Inhibit Proliferation and Migration on Highly Metastatic Cancer Cells, 4T1

Abstract: Brazilein performs anticancer activities on several cancer cells and potentially inhibits metastasis. The aims of this study is to observe the synergistic cytotoxic and migration inhibitory effect of brazilein combined with cisplatin on 4T1 breast cancer cells. Under MTT assay, we found that brazilein revealed cytotoxic effect on 4T1 cells in a dosedependent manner (IC 50 =50 ± 0.3 µM). Combination of brazilein and cisplatin showed synergistic effect (CI=0.72). Flowcytometry analysis on the cell cycle progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…Thus, Li et al reported that after treatment by cisplatin in combination with doxorubicin, extensive areas of necrosis were observed in tumor cells; in other cells, various nuclear abnormalities -nuclear clamping and fragmentation -were revealed. Fragmentation of nuclei (karyorrhexis) may indicate the mechanism of apoptosis in tumor cells [32]. Other authors [32,33] also demonstrated an apoptotic response in 4T1 tumor cells exposed to cisplatin in vitro.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, Li et al reported that after treatment by cisplatin in combination with doxorubicin, extensive areas of necrosis were observed in tumor cells; in other cells, various nuclear abnormalities -nuclear clamping and fragmentation -were revealed. Fragmentation of nuclei (karyorrhexis) may indicate the mechanism of apoptosis in tumor cells [32]. Other authors [32,33] also demonstrated an apoptotic response in 4T1 tumor cells exposed to cisplatin in vitro.…”
Section: Discussionmentioning
confidence: 92%
“…Fragmentation of nuclei (karyorrhexis) may indicate the mechanism of apoptosis in tumor cells [32]. Other authors [32,33] also demonstrated an apoptotic response in 4T1 tumor cells exposed to cisplatin in vitro. In our study, karyorrhexis was observed in tumors of the therapeutic group, which might indicate the mechanism of apoptotic cell death caused by cisplatin.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies revealed antimigratory effects of the flavonoids brazilein and baicalein. 13 , 14 , 37 Secretion of MMP protein in the tumor microenvironment has a role in supporting migration and invasion of cancer cells through ECM degradation. 23 Our study shows the downregulation of MMP2 and MMP9 protein levels by treatment with brazilin alone and its combination with doxorubicin on HER2-overexpressing cells ( Figures 4 C and 4 D).…”
Section: Resultsmentioning
confidence: 99%
“…These data are in line with previous studies which showed that brazilein inhibits MMP2 on MDA-MB-231 cells and that its combination with cisplatin showed downregulation of MMP9 on 4T1 cells. 13 , 14 Other flavonoids, such as 7,7″-dimethoxyagastisflavone, luteolin, quercetin, and a curcumin analog (potassium pentagamavunon-0, K PGV-0), inhibit metastasis through suppression of MMP secretion. 38 - 40 Because NF-κB transcripts MMP protein 41 and HER2 protein has a role on NF-κB protein activation, 42 we drew an inference about the effect of inhibitory effects on migration and invasion by brazilin and its combination with doxorubicin on MCF-7/HER2 cells probably being related to the HER2/NF-κB pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation